Methods of Condition Monitoring of Transformers-Review - Mr. Jameel Ahamad, Imtiyaz Ahmad, Dr. Yaduvir Singh (International Journal of Advanced Science and Technology, 2020)
Condition Monitoring (CM) techniques have been gaining increasing attention these days. CM techniques for electrical equipment have wide many benefits like its application in power plant transformers. As it has huge potential to reduce the operating costs, improve power supply, reduce power supply related issues, and improve customer service, its applications are widening. To pay special attention to the load taking capacity of power transformers a monitoring system has been employed. The system takes the responsibility of scaling the load, voltage, temperatures of some important devices, and the tap changer position. Literature is collected for developing the best possible intelligent CM system with maximized automation, reliability, sensitivity, and advanced practicability. The aim of this research paper is to review the CM techniques that the researchers have selected for review.